Pengesahan Awig-Awig Desa Adat berdasarkan Peraturan Daerah Nomor 4 Tahun 2019 - I Gusti Ayu Mas Mahadewi; I Ketut Sukadana; Luh Putu Suryani (Warmadewa Press, 2020)
Awig-awig is a customary village regulation that can be made in running its government. In the application of the Tri Hita Karana Awig-Awig which is made by the customary village krama / traditional banjar, it is used as a new way to carry out the Tri Hita Karana teachings which must be in accordance with the dharma of religion and the village of mawacara in the local traditional village. In the Awig-Awig task, it requires various processes and is not arbitrary. This research aims to study Awig-Awig and how the process is carried out by Awig-Awig based on regional regulation number 4 of 2019. The method used in this research is a normative legal research method that uses a conceptual approach and a case approach. The first stage of this initial awig-awig step starts from revising existing Awig-Awig and moving awig-awig agenda. Then, the next stage is involved in making the Awig-Awig design. After that, the socialization of the awig-awig design. Fourth, the process of completed the Awig-Awig. The last process in the traditional village paruman was legalized and then the awig-awig was announced openly to all the traditional village krama, then the awig-awig that had been written was registered directly by the Prajuru of the Traditional Village to the provincial apparatus in charge of customary village affairs.